2012
DOI: 10.1159/000332833
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prediction of Exercise-Induced Oxygen Desaturation in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: Previous studies with small sample sizes reported contradicting findings as to whether pulmonary function tests can predict exercise-induced oxygen desaturation (EID). Objective: To evaluate whether forced expiratory volume in one second (FEV1), resting oxygen saturation (Spo2) and diffusion capacity for carbon monoxide (Dlco) are predictors of EID in chronic obstructive pulmonary disease (COPD). Methods: We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 68 publications
3
44
0
Order By: Relevance
“…Severe hypoxemia is relatively uncommon, and long-term administration of oxygen has been shown to increase survival in such patients [5]. Although reports on the prevalence of exertional desaturation without resting hypoxemia in COPD are rare [6,7], some research suggests that exertional desaturation may be a predictor of mortality in these patients with COPD [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Severe hypoxemia is relatively uncommon, and long-term administration of oxygen has been shown to increase survival in such patients [5]. Although reports on the prevalence of exertional desaturation without resting hypoxemia in COPD are rare [6,7], some research suggests that exertional desaturation may be a predictor of mortality in these patients with COPD [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that physical inactivity deteriorates exercise-induced oxygen desaturation [40] and systemic inflammation and results in higher serum levels of interlekin-6 and tumor necrosis factor-α [41,42], which can contribute to osteoporosis [43]. These findings suggest that active patients with higher V·O 2 max levels may have lower levels of these cytokines, resulting in preserved bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen desaturation during a 6MWT provides information regarding exercise-induced desaturation, disease severity, and disease progress. 8 Exercise-induced desaturation is associated with impaired daily physical activity, faster FEV 1 decline, and worse prognosis, 50 which supports its clinical importance.…”
Section: Evaluation Of Deficiencymentioning
confidence: 92%